DAMPAK KONVERSI LAHAN PERTANIAN TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI KABUPATEN KARANGANYAR - Umi Barokah; Suprapti Supardi; Sugiharti Mulya Handayani (Caraka Tani: Journal of Sustainable Agriculture, 2012)
This study aims to (1) analyzing the amount of land conversion and the factors that affect, (2) identify and analyze changes in household income structure of farm households, (3) analyze the impact of conversion on agricultural land to the income distribution, employment and welfare of farm households. The basic method on this study is a descriptive analytic. Determination of the districts location is based on (1) the number of people who worked as farmers themselves, (2) the amount and type of existing industries and (3) ease of reaching the central interconnected economy. Sub-district is elected Jumantono and Jaten. Type of data used include (1) primary data is the results of interviews with farm households, (2) secondary data from relevant instances. The results showed (1) during the 12 years there is a change 0,120 ha of wet rice field function per household farmer and owned land is the only factor affecting the conversion of agricultural land; (2) The proportion of farm income reduced by 8.30% from 42% to 33.7% and the proportion of outside farm income increased 10.30% from 54% to 64.30%), (3) the results of t test analysis with α = 5 % shows the employment and household income of farmers before the conversion is not the same as after the conversion of agricultural land (revenue increased to Rp 1.482 million per year).